2023
DOI: 10.1039/d3cc00050h
|View full text |Cite
|
Sign up to set email alerts
|

Au-modified PtCu nanodendrites as a highly stable and active electrocatalyst

Abstract: A direct galvanic replacement between Au3+ with surface Cu in PtCu3 nanodendrites is applied to synthesize Au modified PtCu3 nanodendrites catalyst (PtCu3-Au), which shows both of superior stability and excellent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Figure 2c has two peaks at 71.0 and 74.4 eV, which correspond to Pt4f , while Figure 2a has two peaks at 314.8 and 330.1 eV that belong to Pt4d . [26] This confirms that platinum (Pt) exists in its zero-valent state in the Pt/GO composite. Calculating the peak area revealed that the composite includes 5.1 mass% Pt, 14.6 mass% oxygen (O), and 80.3 mass% carbon (C).…”
Section: Resultsmentioning
confidence: 54%
“…Figure 2c has two peaks at 71.0 and 74.4 eV, which correspond to Pt4f , while Figure 2a has two peaks at 314.8 and 330.1 eV that belong to Pt4d . [26] This confirms that platinum (Pt) exists in its zero-valent state in the Pt/GO composite. Calculating the peak area revealed that the composite includes 5.1 mass% Pt, 14.6 mass% oxygen (O), and 80.3 mass% carbon (C).…”
Section: Resultsmentioning
confidence: 54%